Cardiac response to hypobaric hypoxia: persistent changes in cardiac mass, function, and energy metabolism after a trek to Mt. Everest Base Camp. - Holloway, C; Montgomery, H; Murray, A; Cochlin, L; Codreanu, I; Hopwood, N; Johnson, A; Rider, O; Levett, D; Tyler, D; Francis, J; Neubauer, S; et al. (2011)
We postulated that changes in cardiac high-energy phosphate metabolism may underlie the myocardial dysfunction caused by hypobaric hypoxia. Healthy volunteers (n=14) were studied immediately before, and within 4 d of return from, a 17-d trek to Mt. Everest Base Camp (5300 m). (31)P magnetic resonance (MR) spectroscopy was used to measure cardiac phosphocreatine (PCr)/ATP, and MR imaging and echocardiography were used to assess cardiac volumes, mass, and function. Immediately after returning from Mt. Everest, total body weight had fallen by 3% (P<0.05), but left ventricular mass, adjusted for changes in body surface area, had disproportionately decreased by 11% (P<0.05). Alterations in diastolic function were also observed, with a reduction in peak left ventricular filling rates and mitral inflow E/A, by 17% (P<0.05) and 24% (P<0.01), respectively, with no change in hydration status. Compared with pretrek, cardiac PCr/ATP ratio had decreased by 18% (P<0.01). Whether the abnormalities were even greater at altitude is unknown, but all had returned to pretrek levels after 6 mo. The alterations in cardiac morphology, function, and energetics are similar to findings in patients with chronic hypoxia. Thus, a decrease in cardiac PCr/ATP may be a universal response to periods of sustained low oxygen availability, underlying hypoxia-induced cardiac dysfunction in healthy human heart and in patients with cardiopulmonary diseases.